2014
DOI: 10.15406/apar.2014.01.00016
|View full text |Cite
|
Sign up to set email alerts
|

Flooding: Abiotic Constraint Limiting Vegetable Productivity

Abstract: Physico-chemical events during flooding Change rhizosphere chemistryExcess water causes a sharp decrease in soil redox potential, AbstractFlooding is a major environmental stress that severely limits crop productivity and it has become a major problem worldwide. More than one third of the world's irrigated area suffers due to flooding, frequently or otherwise. It may result due to heavy rainfall, faulty irrigation, unleveled land, poor drainage or heavy soil texture. Various morpho-physiological, biochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 70 publications
0
14
0
1
Order By: Relevance
“…Drought stress causes stomatal closure, reduces leaf size, stem extension and root proliferation, and disturbs plant water relations (Farooq et al, 2009). Waterlogging leads to reduced oxygen availability, lower root growth, reduced respiration rates, lower nutrient availability and thereby reduced plant growth (Patel et al, 2014;Tewari & Mishra, 2018). Most Earth observation-based GPP models do not include the waterlogging effect, and assume that drought stress is sufficiently captured by the FAPAR and the VPD signals (Stocker et al, 2019).…”
Section: Global Patterns Revealed By Lrf-gppmentioning
confidence: 99%
“…Drought stress causes stomatal closure, reduces leaf size, stem extension and root proliferation, and disturbs plant water relations (Farooq et al, 2009). Waterlogging leads to reduced oxygen availability, lower root growth, reduced respiration rates, lower nutrient availability and thereby reduced plant growth (Patel et al, 2014;Tewari & Mishra, 2018). Most Earth observation-based GPP models do not include the waterlogging effect, and assume that drought stress is sufficiently captured by the FAPAR and the VPD signals (Stocker et al, 2019).…”
Section: Global Patterns Revealed By Lrf-gppmentioning
confidence: 99%
“…It is reported that lenticel formation is associated with ethylene and auxin accumulation due to stress caused by O 2 deficiency in flooded soil (Bruna et al 2012;Patel et al 2014). Flooded roots contain more amount of ethylene and its precursor (acid-1 aminocyclopropane-1-carboxylic acid-ACC), and high activity of ACC synthase and ACC oxidase compared with normal roots (He et al 1996;Rieu et al 2005;Vidoz et al 2010).…”
Section: Tidal Inundationmentioning
confidence: 99%
“…Lack of oxygen disrupts energy supply, ion transport, and membrane integrity, giving rise to nutritional deficiencies in roots and in shoots [38], and plant death occurs due to this lack of oxygen, which results in an energy crisis in the root. Flooding causes increasing severity of diseases [39], and due to the inability of plants to handle the severity and duration of stress, it leads to plant death [6]. Furthermore, death response in periodic flooding causes multiple stress in plants, not only by submergence (flooding) followed by de-submergence (drainage) but also by the presence of more pest and disease infection in high humidity environments post-flooding [28].…”
Section: Ratio Of Survive and Death Plantsmentioning
confidence: 99%